Comparative analysis of PYTHON with other programming languages - Andonov, Filip (Yearbook Telecommunications, 2019)
The goal of this paper is to present a set of criteria for comparison of program languages and give arguments for their selection. With their help The Python language is compared with its competitors for different applications. As a result a methodology for the selection of a program language is developed, based on multi-criteria analysis. The contribution is the developed methodology and the fact that it is universal by nature and can be used for the selection of a different set of languages, criteria and weights.